Pengaruh Program Kesehatan Keselamatan Kerja (K3), Kompensasi, dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan CV. Banyu Sabrang Batik Kulon Progo - Istiqomah, Ervina Fatah; Kirana, Kusuma Chandra; Purnamarini, Tri Ratna (Indonesian Journal Publisher, 2025)
This study aims to examine the influence of Occupational Health and Safety (OHS) programs, compensation, and work environment on employee job satisfaction at CV. Banyu Sabrang Batik Kulon Progo. A quantitative approach was employed, utilizing primary data collected from 60 operational employees. Data analysis was conducted through several stages, including validity and reliability tests, multicollinearity and heteroscedasticity tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²). The findings reveal that the OHS program does not have a significant effect on job satisfaction, suggesting that the implementation of OHS within the company remains suboptimal and fails to enhance employee satisfaction. Conversely, compensation and work environment show a positive and significant impact on job satisfaction. Adequate compensation provides employees with a sense of appreciation for their contributions, while a supportive work environment fosters a sense of safety and comfort in the workplace. The coefficient of determination value of 0.817 indicates that 81.7% of the variation in job satisfaction is influenced by the three variables studied, while the remaining 18.3% is affected by other factors not included in the analysis. These results underscore the importance of fair compensation and a conducive work environment in promoting employee job satisfaction.